Conceptual contributions in marketing scholarship: patterns, mechanisms, and rebalancing options - Kindermann, Bastian; Wentzel, Daniel; Antons, David; Salge, Torsten-Oliver (Technische Universität Dortmund, 2023)
This article analyzes the nature and temporal change of conceptual contributions in marketing scholarship with two complementary studies. First, based on a computer-aided text analysis of 5,922 articles published in the four major marketing journals between 1990 and 2021, the authors analyze how conceptual contributions have changed over time using the MacInnis (2011) framework. Results indicate that over the past three decades, theorizing efforts have strongly favored “envisioning” and “explicating” at the expense of “relating” and “debating,” with this imbalance increasing over time. Second, the authors draw on 48 in-depth interviews with editors, department heads, and authors to validate these patterns and uncover the underlying mechanisms. The findings indicate that a prevalent thought style has developed in the field—defined by the research ideals of novelty, clarity, and quantification—that shapes the collective view of how marketing scholars, in their roles as authors, reviewers, and mentors, can make a valuable contribution to marketing scholarship. This thought style favors envisioning and explicating contributions and disfavors relating and debating contributions. Jointly, the two studies point to several rebalancing options that can reinvigorate relating and debating contributions while preserving the current strengths of the marketing field.
Journal of marketing;88(3)
Keywords: marketing theory; conceptual contribution; sociology of science; thought styles; text analysis; in-depth interviews; 330